2019
DOI: 10.1039/c9ra01848d
|View full text |Cite
|
Sign up to set email alerts
|

Variable temperature solid-state NMR spectral and relaxation analyses of the impregnation of polyethylene glycol (PEG) into coniferous wood

Abstract: To investigate the behaviours of polyethylene glycol (PEG) and its interaction with biomass constituents in coniferous wood (Japanese cypress), variable temperature solid-state NMR spectra and relaxation times were measured from 20–80 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The chemical shifts are analyzed and collected in Table , for all protons of PEG, DOX, and the binary solution. It is seen that the chemical shifts of the protons in P8k were slightly different according to their locations in PEG chain: at 3.68 ppm for the proton on the inner ethylene unit (Ha, Figure A); at 3.75 ppm for the proton on the terminal ethylene unit at the side of the inner ethylene glycol segments (Hb); whereas for the proton on the terminal ethylene unit adjacent to OH (Hc, Figure A), the chemical shift appeared at 3.52 ppm, as reported. The reason that these chemical shifts of the protons (Hb, Hc) appear at higher and lower sides compared to that of the protons on the inner ethylene units (Ha), because the presence of OH, though electrophilic, leads to a slight increase in electron density on its adjacent CH 2 group, as well as on its protons (Hc), in comparison to the protons on the inner ethylene glycol segments; meanwhile, this terminal OH leads to a decrease in electron density on the other CH 2 group (Cb) linked to the inner chain in the terminal ethylene, as well as on its protons (Hb). These assignments were also confirmed by the surface area ratio of the peaks, Ha/Hb/Hc, which was 163/1/1, in good accord with the theoretical ratio for P8k (Ha/Hb/Hc being 170/1/1, M n ≈ 7500).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shifts are analyzed and collected in Table , for all protons of PEG, DOX, and the binary solution. It is seen that the chemical shifts of the protons in P8k were slightly different according to their locations in PEG chain: at 3.68 ppm for the proton on the inner ethylene unit (Ha, Figure A); at 3.75 ppm for the proton on the terminal ethylene unit at the side of the inner ethylene glycol segments (Hb); whereas for the proton on the terminal ethylene unit adjacent to OH (Hc, Figure A), the chemical shift appeared at 3.52 ppm, as reported. The reason that these chemical shifts of the protons (Hb, Hc) appear at higher and lower sides compared to that of the protons on the inner ethylene units (Ha), because the presence of OH, though electrophilic, leads to a slight increase in electron density on its adjacent CH 2 group, as well as on its protons (Hc), in comparison to the protons on the inner ethylene glycol segments; meanwhile, this terminal OH leads to a decrease in electron density on the other CH 2 group (Cb) linked to the inner chain in the terminal ethylene, as well as on its protons (Hb). These assignments were also confirmed by the surface area ratio of the peaks, Ha/Hb/Hc, which was 163/1/1, in good accord with the theoretical ratio for P8k (Ha/Hb/Hc being 170/1/1, M n ≈ 7500).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows that the intensity of the peaks at 83.78 and 88.77 ppm is relatively weak, which is also a manifestation of the decrease of hydroxyl. The NMR of carbon shows that the hemicellulose peaks are located at 23.36, 60.69, 74.83, 105.65 and 177 ppm, representing, respectively, C6 in methoxy, C2-C5 in polysaccharides, C4 in xylan, Cl in hemicellulose, and carbonyl carbon in the acetyl group [28]. According to Figure 5, except for the peak at 21 ppm, the peak intensity of other peaks decreased.…”
Section: Modification Reaction Mechanismmentioning
confidence: 93%
“…In spite of the synthetic polymer, PEG can be fully biodegraded and is used in huge amounts . It was found that long chain PEG molecules were restricted to the cell lumen while the medium and shorter chain PEG molecules penetrated into the intercellular space of the cell wall in addition to the cell lumen . However, the water solubility of PEG would make it easier to leach and limited its utilization in outdoor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…73 It was found that long chain PEG molecules were restricted to the cell lumen while the medium and shorter chain PEG molecules penetrated into the intercellular space of the cell wall in addition to the cell lumen. 74 However, the water solubility of PEG would make it easier to leach and limited its utilization in outdoor conditions. Trey et al improved the durability of PEG in the wood structure through electron-beam initiated polymerization of PEG-based monomers without a catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%